2004
DOI: 10.1080/0264041031000140536
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exercise carbohydrate and fat ingestion: effects on metabolism and performance

Abstract: A key goal of pre-exercise nutritional strategies is to maximize carbohydrate stores, thereby minimizing the ergolytic effects of carbohydrate depletion. Increased dietary carbohydrate intake in the days before competition increases muscle glycogen levels and enhances exercise performance in endurance events lasting 90 min or more. Ingestion of carbohydrate 3-4 h before exercise increases liver and muscle glycogen and enhances subsequent endurance exercise performance. The effects of carbohydrate ingestion on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 87 publications
0
76
2
3
Order By: Relevance
“…Une dépense énergétique accrue due à une activité physique brève ne s'accompagne pas forcément d'une augmentation de l'apport énergétique chez l'individu de corpulence mince et chez l'individu obèse, ce qui se traduit par une diminution de la masse corporelle [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Une étude a montré que la mobilisation des carburants stockés dans le sang joue un rôle dans l'inhibition de la prise alimentaire [4].…”
Section: Effets De L'exercice Sur La Prise Alimentaireunclassified
See 1 more Smart Citation
“…Une dépense énergétique accrue due à une activité physique brève ne s'accompagne pas forcément d'une augmentation de l'apport énergétique chez l'individu de corpulence mince et chez l'individu obèse, ce qui se traduit par une diminution de la masse corporelle [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Une étude a montré que la mobilisation des carburants stockés dans le sang joue un rôle dans l'inhibition de la prise alimentaire [4].…”
Section: Effets De L'exercice Sur La Prise Alimentaireunclassified
“…Il s'avère qu'un repas riche en glucides avant un exercice fait augmenter le glycogène musculaire, baisser la mobilisation des acides gras et augmenter la performance sportive [16,17]. L'amélioration des performances suite à l'ingestion de glucides résulte du maintien du taux de glucose sanguin à la fin de l'exercice.…”
Section: Utilisation Des Substrats éNergétique Lors D'un Exerciceunclassified
“…Several studies report that adherence to a carbohydraterestricted diet can improve athletes' performance, because it can lead to greater fat oxidation and glycogen-sparing effects during exercises [3,4,5]. However other studies indicated consuming high carbohydrate (CHO) diet before exercise enhances subsequent endurance exercise performance [6] and reduces rating of perceived exertion (RPE), especially in high intensive exercises [2,7]. The concept of the glycemic index (GI) is to classify foods based on their actual postprandial blood glucose or white bread [8].…”
Section: Introductionmentioning
confidence: 99%
“…These transient metabolic disturbances, at the start of exercise, as well as mechanisms that increase glycogen utilisation (6,17), may explain why pre-exercise glucose does not always provide an additional benefit in comparison to placebo. Regardless, there now appears to be less concern about the efficacy and use of simple sugars in the hour prior to exercise (18,22,26) despite early reservations regarding rebound hypoglycaemia (6,15). If rebound hypoglycaemia is relevant to endurance performance the use of other forms of CHO, such as galactose, with a low glycaemic index (GI: ~20), which has no primary insulin drive (37), may overcome the issue.…”
Section: Introductionmentioning
confidence: 99%